Hart's Cut, Trinidad - (:unkn) unknown (My University, 2010)
A few observers are standing on the bank of this coconut tree and plants bordered channel, looking on at the occupants of a small sail-boat moored to its sides.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Straits--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Chaguaramas; Hart's Cut (Chaguaramas)